2003
DOI: 10.1080/10715760310001598097
|View full text |Cite
|
Sign up to set email alerts
|

Red-wine Beneficial Long-term Effect on Lipids but not on Antioxidant Characteristics in Plasma in a Study Comparing Three Types of Wine--Description of twoO-methylated Derivatives of Gallic Acid in Humans

Abstract: The purpose of this double clinical study was (1) to evaluate the effect of one single intake (300 ml) of red wine (RW) on the plasma antioxidant capacity (pAOC) and plasma phenolics over the 24-h time period following the intake, and (2) to compare the long-term effects of daily intakes (250 ml/d) of RW, white wine (WW) and Champagne (CH) on the plasma and LDL characteristics of healthy subjects. In the first part, blood samples were collected just before and after wine consumption. In the second part, subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 57 publications
1
41
0
1
Order By: Relevance
“…We only found a transient and significant increase in plasma antioxidant protection 1 h after HT administration, not depending on its determinants albumin, uric acid and bilirubin, suggesting that this effect was due to HT intake. Moreover, this effect might be underestimated because it has been established that pAOC decreases just after a meal, due to the postprandial lipemiaassociated oxidative stress (Cartron et al, 2003). A similar (but not statistically significant) transient effect was shown in rats (Visioli & Galli, 2001).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…We only found a transient and significant increase in plasma antioxidant protection 1 h after HT administration, not depending on its determinants albumin, uric acid and bilirubin, suggesting that this effect was due to HT intake. Moreover, this effect might be underestimated because it has been established that pAOC decreases just after a meal, due to the postprandial lipemiaassociated oxidative stress (Cartron et al, 2003). A similar (but not statistically significant) transient effect was shown in rats (Visioli & Galli, 2001).…”
Section: Resultsmentioning
confidence: 66%
“…b-Carotene was assayed by using the reagent kit for HPLC analysis from ChromSystems (München, Germany). The pAOC determination procedure has recently been described extensively (Cartron et al, 2003). Statistical analyses were performed by means of the Wilcoxon rank sum test by the StatView F4-5 software (Abacus Concepts, Berkeley, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, the distribution of ox-LDL Ab in the unselected population and its relationship with red wine consumption are unknown. In vivo, in the study of Cartron et al (2003) the protective effect of red wine, white wine and French champagne appears to be due to lipid parameter modifications and not to plasma antioxidant characteristics, which showed significant modifications either after a single intake or after a long-term daily intake administration (3 weeks). In our study, in contrast with these results, a reduction in ox-LDL Ab and an increase in TAC were observed after only 4 weeks of daily red wine intake.…”
Section: Discussionmentioning
confidence: 97%
“…An increase in plasma concentration of certain polyphenols after the intake of wine, including catechin, malvidin-3-glucoside, gallic acid, caffeic acid and several metabolites derived from them, has been described [21,[25][26][27]. Although, the aim of this work was to establish whether the intake of a dietary fiber rich in associated PA affected overall plasma antioxidant capacity, it would be necessary in further studies to elucidate the nature of the compounds responsible of the observed increase in this parameter.…”
Section: Acute Intake Of Dietary Fiber Rich In Associated Pamentioning
confidence: 99%